PSYCHOLOGICAL AND PEDAGOGICAL BASIS OF MOTIVATING PERSONAL ACTIVITY IN CREATIVITY (American Journal of Research in Humanities and Social Sciences, 2023)
The article describes the psychological and organizational-pedagogical foundations of motivation for the creative activity of a person. Pedagogical and psychological studies on motivation are analyzed and previously unresolved parts of the general problem for increasing motivation and eliminating them are highlighted.